1976
DOI: 10.1093/brain/99.3.523
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow and Metabolic Rate Early and Late in Prolonged Epileptic Seizures Induced in Rats by Bicuculline

Abstract: Cerebral blood flow (CBF) and cerebral metablic rate for oxygen (CMRO2) have been studied during sustained epileptic seizures induced by bicuculline (1-2 mg/kg, i.v.) in paralysed Wistar rats, artificially ventilated with nitrous oxide/oxygen. CBF was determined by venous outflow collection, and by 133Xe desaturation, using sagittal sinus blood (for cerebral cortical flow) or retroglenoid venous blood (for 'whole brain' flow). The procedure employed ensured that arterial oxygenation remained normal and blood g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
151
3

Year Published

1978
1978
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(169 citation statements)
references
References 0 publications
15
151
3
Order By: Relevance
“…For illustrative purposes, ictal suppression, the LCVR decrease remained sig nificant in the majority of the brain structures (16 of 29 structures). There were no differences in the LCVR changes between the spike, seizure, and suppression states (Table 4) (Plum et aI., 1968;Plum and Duffy, 1975;Meldrum and Nilsson, 1976). However, they expand our un Another factor requires consideration in ex plaining the differences between these two studies.…”
Section: Resultsmentioning
confidence: 80%
“…For illustrative purposes, ictal suppression, the LCVR decrease remained sig nificant in the majority of the brain structures (16 of 29 structures). There were no differences in the LCVR changes between the spike, seizure, and suppression states (Table 4) (Plum et aI., 1968;Plum and Duffy, 1975;Meldrum and Nilsson, 1976). However, they expand our un Another factor requires consideration in ex plaining the differences between these two studies.…”
Section: Resultsmentioning
confidence: 80%
“…(1975). In addition, it has been reported that CMROz was only moderately decreased despite a large decrease in CBF late in recurrent seizures (Meldrum and Nilsson, 1976;Chapman et aI., 1977;Blennow et aI., 1979). Inter pretation of CMROz data must take into account that such measurements indicate steady-state met abolic activity of relatively large tissue volumes.…”
Section: Influence Of Timing Of Repeated Ictal Bursts On Vascular Andmentioning
confidence: 99%
“…In contrast to expectations, sys temic and cerebral vascular responses and associated in creases in cerebral oxygenation were better maintained during long-duration ictal episodes than during short-duLocal brain O2 supply is regulated in proportion to the intensity of local functional activity and met abolic demand (Kuschinsky and Wahl, 1978). The question remains, however, whether this relation ship is maintained during recurrent seizures (Plum et aI., 1974;Meldrum and Nilsson, 1976; Blennow et aI., 1978; Kreisman et aI., 1983a). In previous studies, we demonstrated that there is a transition from oxygen sufficiency to insufficiency in cerebral cortex during recurrent seizures (Kreisman et aI., 1981b(Kreisman et aI., , 1983a.…”
mentioning
confidence: 90%
See 2 more Smart Citations